Quality Of Life in Reflux and Dyspepsia (QOLRAD) Questionnaire in Iranian Patients with GERD: A Validation Study - Tofangchiha, S (Iranian Association of Gastroerterology and Hepatology, 2010)
BACKGROUND Symptoms of gastro-esophageal reflux disease (GERD) affect health-related quality of life (HRQOL). When a questionnaire is translated into a new language, linguistic validation is necessary, yet insufficient, unless the psychometric characteristics have been verified. The aim of this study is to document the translation and psychometric validation of the Persian translation of the Quality of Life in Reflux and Dyspepsia (QOLRAD) questionnaire. METHODS After translation and cultural adaptation of QOLRAD to Persian, fifty patients with clinical GERD from the Prospective Acid Reflux Study of Iran (PARSI) database who had at least one of the symptoms of acid regurgitation, heartburn, non-cardiac chest pain, or dysphagia for at least four weeks over the past three months completed the QOLRAD and Short Form Health Survey-36 (SF-36). After two weeks, QOLRAD was again completed by the patients. Cronbach alpha and Intra-class Correlation Coefficient (ICC) were used to test reliability and Pearson correlation was used to compare the dimensions of SF-36 and QOLRAD. RESULTS The translation was approved by MAPI Research Institute. Fifty patients completed the SF-36 and QOLRAD questionnaires at the first visit. Mean (SD) age of the participants was 38.4 (14.6) years and 68% were females. The internal consistency and reliability of QOLRAD ranged from 0.78–0.92. The test-retest reliability of QOLRAD was from 0.87–0.93. Relevant QOLRAD domains significantly correlated with the majority of SF-36 domains, with the exception of sleep disturbance. CONCLUSION The psychometric characteristics of the Persian translation of QOLRAD were found to be good, with satisfactory reliability and validity.